Integrating Local Wisdom, Customary Law, and National Law in Village Governance: Challenges and the Role of Village Governments - Filmon M. Polin; Yudith F. Lerrick; Tontji Ch. Rafael; Mesi Adu (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
This study examines the challenges and the role of village governments in integrating local wisdom, customary law, and national law in East Kupang District, Kupang Regency, East Nusa Tenggara. Using an empirical legal research method with a qualitative approach, data were collected through in-depth interviews, participatory observation, and document analysis involving village heads, traditional leaders, and community members. The findings show that integration is hindered by limited public understanding of local wisdom and customary law, the absence of formal recognition of customary institutions through village regulations, and legal uncertainty regarding communal land rights. Globalization and modernization have also reduced the relevance of customary norms among younger generations. Village governments play significant roles as facilitators, mediators, and institutional supporters of customary law recognition within the national legal framework. They facilitate stakeholder dialogue, mediate disputes related to customary land and legal practices, and support the preservation of local cultural values through village governance mechanisms. Based on these findings, the study proposes a village-based legal integration model that includes public education, participatory mapping of customary institutions and communal land rights, village regulations recognizing customary practices, village-level dispute resolution forums, involvement of traditional leaders, and district government supervision. The study highlights the importance of participatory and inclusive approaches to integrating customary and national legal systems and recommends strengthening legal recognition, public awareness, and policy support from regional and central governments.